1989
DOI: 10.1111/j.1600-0404.1989.tb03707.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between primitive reflexes, extra-pyramidal signs, reflective apraxia and severity of cognitive impairment in dementia of the Alzheimer type

Abstract: Controversy exists in the literature about the significance of primitive reflexes (PR) and extrapyramidal signs (EP) as diffuse cortical dysfunction signs and their relationship to age and cognitive impairment. A sample of 91 patients with a dementia of the Alzheimer type were examined with a standardized technique to assess the relationship between the finding of PR, EP and severity of cognitive impairment measured by Mini-Mental Status Examination. The value of a short cognitive test, the reflective apraxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
3
2

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 26 publications
2
25
3
2
Order By: Relevance
“…These abnormalities were relatively rare among AD cases in this investigation, however, probably because subjects were selected to be mildly demented at the time of initial examination. Extrapyramidal signs in particu lar are known to be more prevalent among patients with advanced severity of dementia [7,13,14], In view of the small number of cases manifesting these abnormalities in the present study, the lack of association with disease course must be interpreted cautiously. The assessment of psychotic symptoms in the context of the neurologic examination was brief, and a more definitive investiga tion of these factors is in progress, based on the psychiat ric examinations of the same subjects [Ganguli et al" in preparation].…”
Section: Commentmentioning
confidence: 82%
See 1 more Smart Citation
“…These abnormalities were relatively rare among AD cases in this investigation, however, probably because subjects were selected to be mildly demented at the time of initial examination. Extrapyramidal signs in particu lar are known to be more prevalent among patients with advanced severity of dementia [7,13,14], In view of the small number of cases manifesting these abnormalities in the present study, the lack of association with disease course must be interpreted cautiously. The assessment of psychotic symptoms in the context of the neurologic examination was brief, and a more definitive investiga tion of these factors is in progress, based on the psychiat ric examinations of the same subjects [Ganguli et al" in preparation].…”
Section: Commentmentioning
confidence: 82%
“…Presence of primitive reflexes may be correlated with severity of dementia, although this association has not been found consistently in different studies [4][5][6][7], Moreover, because primitive reflexes are also prevalent among normal elderly people [5,8,9], they are not useful for diagnosis of AD. Gait abnormalities are more prevalent in AD than in normal aging [8,10], but are also not useful for diagnosis of AD because a similar short-stepped, bradykinetic gait occurs with normal aging [11], Likewise, extrapyramidal signs may be more prevalent in AD [ 12,13], and their presence is associated with severity of dementia [6,7,14], but qualitatively similar changes occur with normal aging [8,9], These observations highlight the importance of assess ing most neurologic findings in AD in relation to the prevalence of findings among healthy elderly people. In contrast, other findings such as seizures and myoclonus occur in AD [15], but are not features of normal aging.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that in demented patients PRs may have a progressive and determined order of appearance with increasing severity of dementia, with a similar profile in both VaD and AD patients [7]; this finding is believed to reflect a progressive release of brainstem structures from cortical inhibition due to the progression of diffuse cortical atrophy and to a greater ‘cortical dysfunction’ [15]. In this regard, we cannot exclude that some cases of mixed dementia have been included in our VaD population, particularly as the interrater reliability in the diagnosis of VaD has been demonstrated to vary significantly regardless of the criteria used [35].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the aged, a PR per se does not indicate focal or diffuse cerebral disease [12], though a combination of several PRs is frequently considered an indicator of cognitive impairment, even in apparently healthy elderly subjects [13, 14]. A positive correlation between the number of elicitable PRs and the severity of cognitive impairment has been described in both Alzheimer’s disease (AD) and vascular dementia (VaD) [7, 15, 16, 17], two diseases with a similar profile in PR prevalence [7]. We investigated whether the assessment of PRs in an elderly population of chronic ischemic cerebrovascular patients might be an additional warning sign of possible cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…A plausible explanation for reappearance of these re f l e xes in the adult has been the loss of cortical inhibition, resulting from atrophy of normal aging or m ore severe lesions of degenerative dementias [1][2][3][4][5][6][7][8]25 . The term "frontal release signs" for PR seems to be inappropriate, since almost all patients pre s e n ting them had atrophy and hypoperfusion pre d o minantly in posterior regions, and other authors In this study of associations between PR and cognitive perf o rmance, CASI-S showed to be a practical test, easy and quick to administer, suitable for illiterate subjects (that constitute 15% of our population of patients).…”
Section: Discussionmentioning
confidence: 99%